2011
DOI: 10.1890/es11-00323.1
|View full text |Cite
|
Sign up to set email alerts
|

Diet choice of a predator in the wild: overabundance of prey and missed opportunities along the prey capture sequence

Abstract: Citation: Brechbü hl, R., J. Casas, and S. Bacher. 2011. Diet choice of a predator in the wild: overabundance of prey and missed opportunities along the prey capture sequence. Ecosphere 2(12):133. doi:10.1890/ES11-00323.1Abstract. Optimal diet theory (ODT) postulates that predators adjust their foraging decisions by calculating a prey value from the potential biomass gain, handling time, prey vulnerability and encounter rate. Tests of ODT have however so far mainly been restricted to laboratory settings. By vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 50 publications
1
16
0
6
Order By: Relevance
“…Our results, along with several other recent studies (Mayntz et al 2009, Jensen et al 2011, 2012), contribute to the growing evidence that studies of predator diets need to consider more than just energy alone (e.g. optimal diet theory; Schoener 1971, Sih and Christensen 2001, Brechbühl et al 2011), and that macronutrient composition of prey can have large effects on the growth and reproduction of predatory arthropods.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our results, along with several other recent studies (Mayntz et al 2009, Jensen et al 2011, 2012), contribute to the growing evidence that studies of predator diets need to consider more than just energy alone (e.g. optimal diet theory; Schoener 1971, Sih and Christensen 2001, Brechbühl et al 2011), and that macronutrient composition of prey can have large effects on the growth and reproduction of predatory arthropods.…”
Section: Discussionsupporting
confidence: 78%
“…Studies of the foraging ecology of predators have historically focused only on the energy content of prey items (Sih and Christensen 2001, Stephens et al 2007, Brechbühl et al 2011). However, our results contribute to the growing evidence that particular nutrients in prey, such as protein, can have large effects on the fitness of predators (Mayntz et al 2005, Jensen et al 2011, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the probability of surviving each day is [1 − (1.8 × 10 −5 )] 527 = 0.991 (0.998, 0.971) and the expected daily mortality rate is therefore 1% (0.2%, 3%). The voraciousness of the crab spiders in Lincoln County is probably representative because similar capture rates were observed in Bern, Switzerland [Doakland: 0.37% vs. Bern: 0.24%, or two captures in 821 encounters (Brechbühl et al ., )].…”
Section: Methodsmentioning
confidence: 99%
“…Brechbühl, Casas, et al (2010) found that prey capture success was lower than 10% of total visits for most of the flower visitors, except for non-syrphid flies (less specialized flies) whose success was higher than 20%. Brechbühl et al (2011) measured the vulnerability of all flower visitors, and indeed flies were the most vulnerable ones, together with some solitary bees. These were also two groups that were strongly avoiding flowers with spiders (see also Brechbühl, Casas, et al 2010;Brechbühl, Kropf, et al 2010).…”
Section: Interaction Networkmentioning
confidence: 99%